Nutrient transport during bioremediation of contaminated beaches: Evaluation with lithium as a conservative tracer - Wrenn, Brian A.; Suidan, Makram T.; Strohmeier, Kevin L.; Eberhart, B.Loye; Wilson, Gregory J.; Venosa, Albert D. (Water research (Oxford), 1997)
Bioremediation of oil-contaminated beaches typically involves fertilization with nutrients that are thought to limit the growth rate of hydrocarbon-degrading bacteria. Much of the available technology involves application of fertilizers that release nutrients in a water-soluble form prior to bacterial uptake. Oil contamination of coastal areas from offshore spills usually occurs in the intertidal zone. This area is subjected to periodic flooding by a combination of tides and waves, which can affect the washout rate of water-soluble nutrients from the contaminated area. We used lithium nitrate as a conservative tracer to study the rate of nutrient transport in a low-energy, sandy beach on the southwestern shore of Delaware Bay. The rate of tracer washout from the bioremediation zone (i.e. the upper 25 cm below the beach surface) was more rapid when the tracer was applied at spring tide (when the tidal amplitude is largest) than at neap tide, but the physical path taken by the tracer plume was not affected. In both cases, the tracer plume moved vertically into the beach subsurface and horizontally through the beach in a seaward direction. The vertical transport was probably driven by waves infiltrating through the unsaturated zone. Hydraulic gradients that were established by differences between the rate at which the elevation of the water table in the beach changed and the rate at which the tide rose and fell contributed to horizontal movement of the plume.